Motivations and barriers to participation in training programs in Distance Education - Μαγγόπουλος Γιώργος; Σαμαρέντση Βαρβάρα (Education Sciences, 2023)
The purpose of this paper is to indicating the views of primary education teachers regarding the motivations and barriers to their participation in training programs in distance education. At the methodological level, the sampling research was adopted by utilizing the questionnaire as a data collection tool. The research sample consists of 138 teachers. Respondents believe that distance education training programs should primarily address their own needs. Their participation motivations are mainly related to the realization of their professional role. Inhibitory factors relate to institutional and situational barriers. Gender, teaching experience and employment relationship differentiate the teachers of the sample in terms of participation motivation, while age and place of residence do not differentiate them. Their age, teaching experience, employment relationship and place of residence differentiate them in terms of barriers to participation, while gender does not differentiate them.